Contesting the Portrayal of Beauty As It is in Music Videos: A Semiotic Analysis of the Video of Yura Yunita-Tutur Batin - Dini Okta Lamdia; Anang Dwi Santoso; Rindang Senja Andarini (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Recently,